Implikasi Tugas-Tugas Perkembangan Remaja dalam Penyelenggaraan Pendidikan di SMK: Implications of Adolescent Developmental Tasks in Implementation of Education in SMK - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Adolescence is often associated with myths and stereotypes regarding deviance and abnormality. This can be seen from the many developmental theories that discuss incongruity, emotional disturbances and behavioral disturbances as a result of the pressures experienced by adolescents due to changes that occur to them and due to changes in the environment. In line with the changes that occur in adolescents, they are also faced with tasks that are different from those in childhood. As is known, in every phase of development, including in adolescence, individuals have developmental tasks that must be fulfilled. If these tasks are successfully completed, satisfaction, happiness and acceptance from the environment will be achieved. Individual success in fulfilling these tasks will also determine individual success in fulfilling developmental tasks in the next phase. Hurlock (1973) defines adolescence based on chronological age, which is between 13 and 18 years. According to Thornburgh (1982), this age limit is a traditional limit, while contemporary schools limit the age of youth between 11 to 22 years.